A cartilha midiática de Capricho para a educação da jovem brasileira - Mesquita, Letícia Nassar Matos (2014)
This study has as its theme the prescriptive discourse of the press media directed at the young female audience in Brazil. The corpus is CAPRICHO magazine, which has been published by Editora Abril since 1952. Currently this magazine is the publication for young girls with the largest circulation in the country. The issues under study were published in the period from January 2010 to December 2011, among these, 27 issues from 2010 and 25 from 2011. Our aim was to analyze how the discursive and narrative strategies impose on youth values in circulation in the magazine which enable the young readers to develop skills , attitudes and behaviors, turning the publication into a media booklet that teaches certain modes of presence in the world that constitute the Capricho way of being. Our thesis is that CAPRICHO is a didactic communication vehicle, a sort of booklet that dictates behavior, ways of being in the world, highlighting gender issues, especially regarding young Brazilian girls. To defend this thesis, the following hypotheses were tested: a) the Capricho way of being is built by reiterations of discursive and narrative strategies that contribute to the circulation of social values and axiologies; b) the syncretism of languages plays a major role in convincing the readers; c) the intersubjective interaction of intimacy is what characterizes the close interaction between enunciator and enunciatee, marking the acts of advising and following the advice; d) the manipulation strategy of seduction covers the prescriptive discourse which is valued as a daily participant; e) due to this condition of daily routine presence, CAPRICHO is valued as a manual that helps to make sense to the being in the world, the magazine is considered as an object of collection; f) as an accessible manual, it can leave the shelf according to the needs of the young readers. The analysis is based on the theoretical and methodological contributions of discoursive semiotic. The analysis is based on the theoretical and methodological contributions of discoursive semiotic, focusing on studies about syncretism of languages. As a result, it was found that as CAPRICHO uses rich plasticity and words taken from the young enunciatee, the reader is subjected to the social values attributed to Brazilian women: kindness, sociability linked to aesthetics and the importance of studying for the working market. Consumerism is embedded in each part of the magazine, like a driving force which makes the reader believe to be the addresser. The relevance of this thesis is also to prove that the analyzes of the relationship between visual and verbal writing are essential for grasping the meaning of a syncretic text and building a critical reader